2022
DOI: 10.3390/toxins14030189
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Exposure during the First 1000 Days of Life and Its Impact on Children’s Health: A Clinical Overview

Abstract: The first 1000 days of life are very sensitive to any event that alters health programming, and they represent a window for intervention to improve population health. Pregnant women, fetuses, and infants are particularly vulnerable to exposure to food contaminated with mycotoxins. This review aimed to gather data from the literature on mycotoxins exposure during intrauterine life and early childhood, and associated health risks, as assessed through human biomonitoring and mycotoxins occurrence in foods, in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…The International Agency for Research on Cancer (IARC) classify AFs as class 1 carcinogens ( IARC, 2002 ). Aflatoxins have been associated with liver cancer ( Kimanya et al, 2021 ), retarded fetal growth in utero and infants ( Alvito & Pereira-da-Silva, 2022 ), as well as immunosuppression ( El miniawy et al, 2014 ). Aflatoxins in animals have been linked to reduced productivity, increased incidence of diseases, damage to vital organs, and death ( Robens and Richard, 1992 ).…”
Section: Introductionmentioning
confidence: 99%
“…The International Agency for Research on Cancer (IARC) classify AFs as class 1 carcinogens ( IARC, 2002 ). Aflatoxins have been associated with liver cancer ( Kimanya et al, 2021 ), retarded fetal growth in utero and infants ( Alvito & Pereira-da-Silva, 2022 ), as well as immunosuppression ( El miniawy et al, 2014 ). Aflatoxins in animals have been linked to reduced productivity, increased incidence of diseases, damage to vital organs, and death ( Robens and Richard, 1992 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, FGR in human fetuses has been associated with maternal exposure to environmental pollutants (Gómez-Roig et al, 2021). For instance, maternal exposure to airborne pollutants, mycotoxins, phthalates, as well as to drinking water contaminated with nitrate and pesticide, has been linked to a higher occurrence of FGR (Alvito and Pereira-da-Silva, 2022; Bach et al, 2015; Chang et al, 2022; Gönenç et al, 2020; Macchi et al, 2021; Santos et al, 2021; Smith et al, 2017)As our study demonstrates for the first time a small but consistent growth delay in mice embryos upon maternal exposure to an environmental level of CBZ, further studies are needed to determine whether the mild growth restriction found in the CBZ-exposed mice at GD9.5 persists throughout gestation, in order to conclude whether CBZ from the environment may induce FGR in mice, which may be comparable to clinical evidences in humans (Dilworth et al, 2011). If so, it would appear necessary to begin exploring whether higher incidences of FGR are detected in regions with relatively high levels of CBZ in treated wastewater, surface water and groundwater.…”
Section: Resultsmentioning
confidence: 99%
“…This may happen in the occupational environments as those related with the working areas where raw materials and waste are handled (field, silos, small enterprises, etc.) or through food ingestion [ 21 , 22 , 23 ]. For example, in Europe and America where maize is used as an energy source in animal feed with an incorporation rates ranging between 50% and 80% of the diets [ 11 ], the limits established for aflatoxins and for DON were already exceeded [ 11 , 24 ], which is a real concern.…”
Section: Discussionmentioning
confidence: 99%